1930 Conn. Stat. 903, Dealing in Explosives; License., ch. 147, § 2644 - (:unkn) unknown (General Publisher, 1930)
Prohibited the manufacture, storage, sale, or dealing in gunpowder or any material defined as an explosive in § 2638
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER